Pemanfaatan Cacing Tanah (Lumbricus rubellus) Dalam Mendekomposisi Limbah Organik dan Mengahasilkan Pupuk Vermikompos di Desa Kubucolia Kec. Dolat Rakyat Kab. Karo - Nursiani Lubis; Mazlina Mazlina; Try Koryati; Wiwik Yunidawati; Eliakim Purba (Jurnal Pengabdian Kepada Masyarakat Digital, 2022)
The making of vermicompost by involving the role of this worm can reduce pollution from organic waste. The more worm cultivation, the greater the absorption of waste/garbage from the environment so that environmental pollution due to piles of organic waste can be reduced. Earthworms also have the ability to convert insoluble nutrients into soluble forms with the help of enzymes contained in the digestive tract of worms, so that plants absorb them more quickly. the development of organic farming systems provides opportunities for the development of vermicompost on a wider scale. This not only has a positive effect on improving soil fertility but also opens up profitable business opportunities. The purpose of this activity is to provide insight to farmers regarding the use of earthworms (Lumbricus rubellus) in converting organic wastes into vermicompost, which can be used as organic fertilizer in plant cultivation. The method used in this activity is to give lectures about earthworms and vermicompost, conduct discussions and questions and answers, and practice vermicompost activities. The impact obtained is an increase in the knowledge of farmers regarding the role of earthworms in vermicompost or indirectly about the role of earthworms in agriculture.Keywords: Vermicompost, Earthworm (Lumbricus rubellus), Organic waste